Effect of fiber type on the level of stress concentration created in filleted composite rectangular bars in bending - Gur, Mustafa; Turgut, Aydin; Sancaktar, Erol (ASME, 1995)
The effect of fiber type on the level of stress concentration created by fillets were investigated for unidirectional rectangular laminates loaded on or off-axis in bending. The finite element method was used for this purpose utilizing 4-node quadrilateral elements under plane stress conditions. Analyses were performed for three different fiber reinforcements of epoxy matrix: glass, graphite and boron. Typical material properties reported in the literature for glass/epoxy, boron/epoxy and graphite/epoxy were used in calculations.
Proceedings of the 1995 ASME International Mechanical Engineering Congress and Exposition -- 12 November 1995 through 17 November 1995 -- San Francisco, CA, USA -- 44144
Keywords: Bending (deformation); Finite element method; Glass fiber reinforced plastics; Graphite fiber reinforced plastics; Laminated composites; Mechanical properties; Stress concentration; Composite rectangular bars; Four node quadrilateral elements; Plane stress; Composite structures